Do R&D subsidies matter? Evidence for the German service sector - Dirk Czarnitzki; Andreas Fier (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2001)
In recent times the service sector is often called the driving force of today?s economies. This paper analyses the innovative activities of German service firms. We investigate whether firms that receive public subsidies for innovation projects engage more in innovative activities than others. Additionally, we test the hypothesis that innovative firms are more likely to get public grants in the future. Empirically, it turns out that public grants raise the firms? privately financed innovative activities. The more grants a firm has received in the past, the more it invests in current innovation projects. Furthermore, innovating firms are more likely to have future access to public grants. Additionally, the share of university graduates of firms' total employees is an important factor for future participation in public R&D schemes.
Keywords: H32; C24; O31; C20; 330; Innovation; Public R&D Subsidies; Service Sector; Policy Evaluation; Forschungssubvention; Dienstleistungssektor; Innovation; Wirtschaftspolitische Wirkungsanalyse; Deutschland